Small supernumerary marker chromosomes: A legacy of trisomy rescue?. Issue 2 (22nd November 2018) - Kurtas, Nehir Edibe; Xumerle, Luciano; Leonardelli, Lorena; Delledonne, Massimo; Brusco, Alfredo; Chrzanowska, Krystyna; Schinzel, Albert; Larizza, Daniela; Guerneri, Silvana; Natacci, Federica; Bonaglia, Maria Clara; Reho, Paolo; et al.
Abstract: We studied by a whole genomic approach and trios genotyping, 12 de novo, nonrecurrent small supernumerary marker chromosomes (sSMC), detected as mosaics during pre‐ or postnatal diagnosis and associated with increased maternal age. Four sSMCs contained pericentromeric portions only, whereas eight had additional non‐contiguous portions of the same chromosome, assembled together in a disordered fashion by repair‐based mechanisms in a chromothriptic event. Maternal hetero/isodisomy was detected with a paternal origin of the sSMC in some cases, whereas in others two maternal alleles in the sSMC region and biparental haplotypes of the homologs were detected. In other cases, the homologs were biparental while the sSMC had the same haplotype of the maternally inherited chromosome. These findings strongly suggest that most sSMCs are the result of a multiple‐step mechanism, initiated by maternal meiotic nondisjunction followed by postzygotic anaphase lagging of the supernumerary chromosome and its subsequent chromothripsis. Abstract : Possible fates of the supernumerary chromosome present in a trisomic zygote, as a consequence of partial trisomic rescue. After anaphase lagging and massive shattering in the context of a chromothripsis event, the saved portion(s) of the supernumerary chromosome may lead to a final karyotype with a small supernumerary marker chromosome (sSMC), or with 46 chromosomes and a de novo unbalanced translocation or a de novo unbalanced insertional translocation.